c-Myb regulates NOX1/p38 to control survival of colorectal carcinoma cells - Pekarčíková, Lucie; Knopfová, Lucia; Beneš, Petr; Šmarda, Jan (Cellular signalling, 2016)
The c-Myb transcription factor is important for maintenance of immature cells of many tissues including colon epithelium. Overexpression of c-Myb occurring in colorectal carcinomas (CRC) as well as in other cancers often marks poor prognosis. However, the molecular mechanism explaining how c-Myb contributes to progression of CRC has not been fully elucidated. To address this point, we investigated the way how c-Myb affects sensitivity of CRC cells to anticancer drugs. Using CRC cell lines expressing exogenous c-myb we show that c-Myb protects CRC cells from the cisplatin-, oxaliplatin-, and doxorubicin-induced apoptosis, elevates reactive oxygen species via up-regulation of NOX1, and sustains the pro-survival p38 MAPK pathway. Using pharmacological inhibitors and gene silencing of p38 and NOX1 we found that these proteins are essential for the protective effect of c-Myb and that NOX1 acts upstream of p38 activation. In addition, our result suggests that transcription of NOX1 is directly controlled by c-Myb and these genes are strongly co-expressed in human tumor tissue of CRC patients. The novel c-Myb/NOX1/p38 signaling axis that protects CRC cells from chemotherapy described in this study could provide a new base for design of future therapies of CRC.
Keywords: NADPH oxidase; Proto-Oncogene Proteins c-myb; reaktivní formy kyslíku; NADPH-oxidasy; regulace genové exprese u nádorů; Colorectal carcinoma; Reactive Oxygen Species; c-Myb; Doxorubicin; viabilita buněk; aktivace enzymů; Enzyme Activation; Animals; Oxidative Stress; NADPH Oxidases; Signaling pathway; NADH, NADPH oxidoreduktasy; Humans; Mice; cisplatina; sekvence nukleotidů; protoonkogenní proteiny c-myb; doxorubicin; kolorektální nádory; NADH, NADPH Oxidoreductases; oxidační stres; p38 Mitogen-Activated Protein Kinases; organoplatinové sloučeniny; vazebná místa; promotorové oblasti (genetika); RNA, Messenger; Oxaliplatin; Colorectal Neoplasms; Cell Line, Tumor; Reactive oxygen species; Organoplatinum Compounds; oxaliplatin; nádorové buněčné linie; zvířata; apoptóza; Cell survival; Gene Expression Regulation, Neoplastic; Base Sequence; upregulace; Binding Sites; NADPH Oxidase 1; Promoter Regions, Genetic; NADPH-oxidasa 1; Cell Survival; lidé; messenger RNA; Cisplatin; Up-Regulation; Apoptosis; myši; mitogenem aktivované proteinkinasy p38